Pelatihan Penyusunan Asesmen Tema Gaya Hidup Berkelanjutan pada Projek Penguatan Profil Pelajar Pancasila - Nurfitra Yanto; Ramlawati Ramlawati; Zulqifli Alqadri; St. Mutia Alfiyanti Muhiddin; Yahya Yahya (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2024)
Pancasila Student Profile Strengthening Project (P5) is part of the Independent Curriculum which aims to build student character based on Pancasila values. One of the main themes in P5 is a sustainable lifestyle, this theme is designed to increase students' awareness of the importance of maintaining ecosystem balance and practicing an environmentally friendly lifestyle. This community service activity was carried out by a team of lecturers from the FMIPA Science Education Study Program, Makassar State University in collaboration with the Bulukumba Regency Science MGMP. This activity, which took place offline on 27–28 July 2024, involved 63 middle school and high school/equivalent teachers. Training methods include guidance, mentoring, and direct practice in preparing P5 assessments with the theme of sustainable lifestyles, such as making ecoenzyme-based soap. The results of the activity showed high enthusiasm from the participants, most of whom came from schools that had just implemented the Independent Curriculum. However, several obstacles related to the implementation of project-based assessments are still found, such as difficulties in compiling rubrics and understanding authentic assessments in depth. This training makes a positive contribution in increasing teacher competency to prepare and implement project-based assessments in accordance with the Independent Curriculum rubric. Apart from that, it is hoped that this training will be able to equip teachers to guide students in building creative, innovative and environmentally conscious characters through the theme of a sustainable lifestyle.